HARUM SUNDAL MALAM (POLIANTHES TUBEROSA) AS AN INSPIRATION ON BATIK DESIGN: AN ETHNOMATHEMATICAL STUDY - Wan Norliza Wan Bakar; Junaidi Awang; Saipudin Hasbullah (Journal of Islamic, Social, Economics and Development, 2024)
Bunga Harum Sundal Malam or its scientific name Polianthes Tuberosa is an incredibly unique plant in Malay society. This flower has a seductive aroma of fragrant night flower with everlasting scent and is often used in wedding ceremonies in Indonesia, India, and Hawaii. It has an aromatherapy property that can reduce stress and have a healing effect. The uniqueness of this flower has given an inspiration to the batik designer to design on batik. This paper discusses ethnomathematical studies on Bunga Harum Sundal Malam as an inspiration of batik design. Triangulation method of observation, interview and analysis of motifs were used. The result showed that the geometrical elements of “bunga harum sundal malam” or Polianthes Tuberosa are circle, rectangle, and half circle. The flower motifs were arranged in tessellation. Further research can be developed to study other arrangements of the flower.